Equity and Efficiency in Women-Empowered Contract Farming: An Explanatory Case Study on the Tea Estate Sector of Sri Lanka - Dishanka, Sajitha; Sakurai, Takeshi; Ikemoto, Yukio (Journal of Economics and Behavioral Studies, 2022)
Essentially, equity and efficiency are integral parts of any economic activities of sustainability though the correlation and causation between those two constructs are not considered significant. This study intends to evaluate if the contract farming system is a sustainable solution to the prevailing socio-economic aspects of the labor productivity problem in the tea estate sector of Sri Lanka, where female workers are highly depressed. This study has employed the survey strategy within the instrumental case of a selected tea estate to assess equity and efficiency of women-empowered contract farming system. The analytical results for gender equity on input and performance indicators have proven that gender equity is maintained in contract farming at the sample tea estate. The efficiency analysis results revealed that the output elasticity of tea bushes is significantly lower for female farmers than male farmers. However, there is no such significant difference revealed in the output elasticity of labor between gender groups. These findings explicitly reveal that the female workers in the tea estate sector are capable of managing labor although they are dominated by males in the domesticity. It further implies that a transformation of the male-dominant culture of the tea estate community would enhance the entrepreneurial and leadership capabilities of female workers if they are provided with equal opportunities and freedom.